MENGEMBANGKAN REGULASI DIRI MELALUI PEMBERIAN PENGHARGAAN - WAHYUNINGTYAS, DESSY PUTRI (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The purpose of this study is to explain the process and out come of the reward system that can improve self-regulation in group BPKK kindergarten Lidah Kulon II Surabaya in 2014.This study uses the Kemmis and Mc Taggart procedures which consists of four phases: planning, action, observation and reflection. The data analysis techniqueconsistedofqualitative anddescriptive statistics are presented in tables and graphs. Qualitative data analysis using the techniques according to Miles and Huberman which consists of data reduction, data display, and verification collected through self-regulation instruments, interviews, field notes, and documentation. After the first cycle of action, the average value of 68,47%. Then after second cycle of action, the average value increase to 84,17%. It can be concluded that by using the method of reward can improve self regulation in children. Keywords: self regulation, reward, Early Chilhood